Learning English from YouTubers: English L2 learners' self-regulated language learning on YouTube. Issue 4 (7th August 2020) - Wang, Hung-chun; Chen, Cheryl Wei-yu
ABSTRACT: Focusing on a growing English-learning trend in Taiwan, this study investigated EFL university students' self-regulated language learning on YouTube outside of the classroom. Twenty university students who had substantial experience of watching YouTubers' English-teaching videos were invited for an individual interview to bring to light their perceptions of this self-directed learning approach. Their responses were analyzed to provide insights into learners' attitudes toward this technology-enhanced learning strategy and its impact on their learning of English. Results show that the most highlighted purposes for learning English on YouTube were to explore more learning resources, to seek the attraction of learning English, and to explore cultural knowledge. After viewing the videos on YouTube, the students were more likely to press like and share the videos with their friends. Moreover, learning English on YouTube was considered to be more flexible, more interesting, and more interactive than formal learning in the classroom; nevertheless, this informal learning approach was also deemed less effective for students who wanted to improve their English or prepare for English exams. Based on the results, this study concludes by highlighting the pedagogical implications of this research and proposing the complementary use of YouTubers' English-teaching videos to classroom learning.